WORK-FAMILY CONFLICT AND EMOTIONAL EXHAUSTION: THE IMPACT ON THE PERFORMANCE OF FEMALE EMPLOYEES WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE - Amalia, Mei Rani; Subroto, Setyowati; Nurbaeti, Hani (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study was conducted to determine the implications of work-family conflict and emotional exhaustion on the performance of female employees during the COVID-19 pandemic with organizational commitment as a mediation variable, a case study at the Tegal City Health Office. The authors in this study were all 48 female employees of the Tegal City Health Office who were married and had civil servant status. The sampling technique used saturated sampling by taking the population as a sample. The data analysis technique used in this study was the partial least square (PLS) method with SmartPLS software version 3.0.Â The results of this study explain that Work-family conflict and emotional exhaustion have negative and significant implications for organizational commitment and employee performance. In contrast, organizational commitment had a positive and significant impact on employee performance.